Mold powder for continuous casting and method of making steel

JP2025036126AActive Publication Date: 2025-03-14JFE STEEL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024110500
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-24
Filing Date
2024-07-09
Publication Date
2025-03-14
Estimated Expiration
2044-07-09

AI Technical Summary

Benefits of technology

【0019】 本発明によれば、高Al鋼を連続鋳造する際に、高品質な鋳片の製造及び操業トラブルの防止を可能とする連続鋳造用モールドパウダーを提供することができる。また、前記パウダーを用いた鋼の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036126000003
    Figure 2025036126000003
  • Figure 2025036126000004
    Figure 2025036126000004
  • Figure 2025036126000001
    Figure 2025036126000001
Patent Text Reader

Abstract

To provide a mold powder for continuous casting capable of producing a quality slab and prevent operation troubles in carrying out continuous casting of high-Al steel.SOLUTION: A mold powder for continuous casting comprises a component composition consisting of at least one oxide selected from a group consisting of CaO, BaO, MgO, La2O3, and ZrO2, aggregate carbon, Al2O3, a fluorine compound, Li2O, and a remainder of inevitable impurities and has a content of Al2O3: 25-35 mass%, a total content of Ca, Ba, Mg, La, and Zr in terms of oxide: 40-60 mass%, a content of F :3-10 mass%, a content of Li in terms of Li2O: 6-12 mass%, and a total content of the inevitable impurities: 0-2.0 mass%, so as to have Y expressed by -12.7×(%C)+51.8 of 5 or greater and 35 or smaller.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a mold powder for continuous casting and a method for producing steel. [Background technology]

[0002] When molten steel is continuously cast using a continuous casting machine, first, the molten steel is poured from a ladle through a tundish into a mold, and an initial solidified shell is formed in the mold. The molten steel is then cooled in the subsequent secondary cooling zone, and solidification progresses to the inside. During casting, mold powder for continuous casting (hereinafter sometimes referred to as powder) is constantly added to the mold, and the molten powder penetrates between the mold and the solidified shell. In continuous casting, the powder plays a role in improving the lubrication between the solidified shell and the mold, as well as in keeping the molten steel warm.

[0003] Generally, powders are composed mainly of CaO and SiO2, with other ingredients such as Al2O3, Na2O, fluorine compounds, and C being added depending on the desired characteristics. Here, SiO2 is added to lower the melting point and promote vitrification. However, if the Al concentration in the molten steel is high, a thermite reaction occurs during continuous casting, and the oxides in the powder, especially SiO2, are reduced by the Al in the molten steel. The thermite reaction between SiO2 and Al is expressed by the following formula (1). 4[Al]+3(SiO2)→2(Al2O3)+3[Si]……(1) Here, [Al] and [Si] refer to the components in the molten steel, and (SiO2) and (Al2O3) refer to the components in the powder.

[0004] The thermite reaction increases the Al2O3 concentration in the powder. It is known that an increase in the Al2O3 concentration in the powder can cause various problems. For example, when continuous casting is performed using powder containing CaO and SiO2, the increase in the amount of Al2O3 produces 2CaO·Al2O3·SiO2 (gehlenite), which has a high melting point. Gehlenite significantly deteriorates the lubricity of the powder, increasing the risk of an operational problem called breakout, in which the initial solidified shell breaks during casting and molten steel leaks out. Furthermore, the melting point increases with the increase in the Al2O3 content, and a mass of sintered powder called bare is produced on the mold. When the bare becomes coarse, it pushes the initial solidified shell, which can cause a depression on the surface of the cast piece.

[0005] In light of this background, various powders have been proposed for continuous casting of high-Al steels in order to produce high-quality cast pieces and prevent operational problems.

[0006] For example, Patent Document 1 proposes a mold powder for continuous casting of steel, characterized in that the F content is 16-25 mass%, the mass ratio of CaO to SiO2 (CaO / SiO2) is 1.0-1.8, the Al2O3 content is 5 mass% or less (including zero), and the MgO content is 1.5 mass% or less (including zero). It is said that this powder can prevent restrictive breakouts and enlargement of slag bears caused by large compositional fluctuations. Here, the compositional fluctuation refers to a decrease in SiO2 and an increase in Al2O3 in the molten slag.

[0007] Patent Document 2 proposes a mold powder for continuous casting, which contains 10-35wt% CaO, 10-35wt% Al2O3, 3-15wt% TiO2, 3-20wt% Li2O, 5-40wt% BaO, 15wt% or less F, 20wt% or less Na2O, and one or more of 0.5-4.0wt% BN and 0.5-4.0wt% C as aggregates, with the remainder being unavoidable impurities. It is said that this powder can prevent deterioration of the slab surface quality and breakouts caused by poor lubrication (alteration) of the powder when continuously casting steel containing slag-reducing metal elements. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2017-170494 A [Patent Document 2] Japanese Patent Application Publication No. 5-185195 Summary of the Invention [Problem to be solved by the invention]

[0009] However, the powder described in the above document has the following problems.

[0010] For example, the powder described in Patent Document 1 contains SiO2, and therefore a thermite reaction occurs when it is used. The thermite reaction not only increases the Al2O3 concentration in the powder, but also generates heat, which causes problems. First, the solidification of the molten steel is delayed at the meniscus, causing the solidified shell to break (bleed) along the oscillation mark. This impairs the surface quality of the slab. Furthermore, the generation of flames can cause equipment failure and shutdown of operations.

[0011] In addition, the powder described in Patent Document 2 does not contain SiO2, but contains Na2O and TiO2, and a thermite reaction proceeds between these components and Al in the molten steel. As a result, operational troubles occur and the quality of the slab deteriorates due to the increase in heat generation and Al2O3 concentration. [Means for solving the problem]

[0012] The gist of the present invention for solving the above problems is as follows.

[0013] 1. Aggregate carbon, Al2O3, At least one oxide selected from the group consisting of CaO, BaO, MgO, La2O3, and ZrO2; Fluorine compounds, LiO, and the remainder being unavoidable impurities, Al2O3 content: 25~35% by mass, Total content of Ca, Ba, Mg, La, and Zr calculated as oxide: 40 to 60 mass%, F content: 3~10% by mass, Li content in terms of Li2O: 6 to 12 mass%, The total content of the unavoidable impurities is 0 to 2.0% by mass, A mold powder for continuous casting, wherein Y, represented by the following formula (2), is 5 or more and 35 or less, when the content of the aggregate carbon expressed in mass % is (%C). Y = -12.7 × (%C) + 51.8 …… (2)

[0014] 2. The composition of the components further comprises 2. The mold powder for continuous casting according to claim 1, containing a carbonate of at least one element selected from the group consisting of Li, Ca, Ba, Mg, La, and Zr.

[0015] 3. The mold powder for continuous casting according to 1 or 2 above, wherein the maximum particle size of the mold powder is 250 μm or less.

[0016] 4. The mold powder for continuous casting according to any one of 1 to 3 above, wherein 50 mass % or more of the mold powder is made of a premelt raw material.

[0017] 5. A method for producing steel, comprising continuously casting steel containing 0.5 mass % or more of Al using the mold powder for continuous casting as defined in any one of 1 to 4 above.

[0018] 6. A method for producing steel as described in 5 above, wherein the powder consumption per ton of molten steel is 0.4 kg or more. Effect of the Invention

[0019] According to the present invention, it is possible to provide a mold powder for continuous casting that enables production of high quality cast pieces and prevention of operational problems when continuously casting high Al steel, and a method for producing steel using the powder. [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 is a graph showing the relationship between the molten layer thickness and the number of temperature reversals between the upper and lower thermocouples. [Diagram 2] FIG. 2 is a graph showing the relationship between the molten layer thickness and the number density of powder defects. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The present invention will be specifically described below. In this specification, "%" as a unit of content refers to "% by mass" unless otherwise specified.

[0022] As described above, when the Al2O3 concentration of the powder increases, the formation of gehlenite with a high melting point and the coarsening of bare grains occur, which impairs the stability of operation and reduces the surface quality of the cast slab. Therefore, in order to obtain stable productivity and quality in the continuous casting of high-Al steel, it is desirable to keep the increase in the Al2O3 concentration of the powder during casting as small as possible.

[0023] The factors that cause the Al2O3 concentration in powder to increase during casting include the oxidation of Al in the molten steel by oxides in the powder and the oxidation of Al in the molten steel by the atmosphere. Since it is difficult to prevent oxidation by the atmosphere, it is necessary to prevent the oxidation of Al in the molten steel by oxides in the powder as much as possible in order to reduce the increase in the Al2O3 concentration. In addition, in order to manufacture steel without causing problems with operation and quality, it is necessary to set the powder preparation and steel manufacturing conditions taking into account the fact that the Al2O3 content in the powder will increase to a certain extent during casting.

[0024] As a result of investigations from the above viewpoints, the inventors focused on the solidification start temperature after the powder changes in composition during casting. The inventors then came to the conclusion that it is preferable to lower the solidification start temperature after the change in composition (hereinafter, the solidification start temperature after the change in composition may be simply referred to as the solidification start temperature). In order to lower the solidification start temperature, the composition of the powder and the manufacturing conditions of the steel are important.

[0025] The component composition of the powder according to one embodiment of the present invention will be described below.

[0026] First, the content of each component will be described. In this specification, the content of each component is a normalized value such that the sum of the content of the metal element in terms of oxide and the content of elements excluding the metal element and O (oxygen) is 100%. The above normalization is applied to the total C content, the Al2O3 content, the contents of Ca, Ba, Mg, La, and Zr in terms of oxide, the F content, the Li content in terms of Li2O, the aggregate carbon content, and the unavoidable impurity content.

[0027] For example, in the case of a mold powder whose component elements are C, Al, Ba, Ca, Li, Mg, F, and O, the content is determined as follows: First, the content of each component other than O in 100 mass% of the mold powder (%TC', %Al', %Ba', %Ca', %Li', %Mg', %F') is measured by the method described later. Next, the contents of Al, Ba, Ca, Li and Mg calculated as oxides (%Al2O3´, %BaO´, %CaO´, %Li2O´, %MgO´) are calculated using %Al´, %Ba´, %Ca´, %Li´ and %Mg´. Next, a coefficient (100 (mass%) ÷ A (mass%)) is calculated from the total A (mass%) of the contents of Al, Ba, Ca, Li, and Mg converted into oxides, the C content, and the F content, and the content of each component is normalized by multiplying the content of each component by the coefficient. Specifically, the content of each component is normalized by the following formula. A=%TC´+%Al2O3´+%BaO´+%CaO´+%Li2O´+%MgO´+%F´……(3-1) %TC=%TC´÷A×100……(3-2) %Al2O3=%Al2O3´÷A×100……(3-3) %BaO=%BaO´÷A×100……(3-4) %CaO=%CaO´÷A×100……(3-5) %Li2O=%Li2O´÷A×100……(3-6) %MgO=%MgO´÷A×100……(3-7) %F=%F´÷A×100……(3-8) Here, %TC and %F are the normalized total C content and F content, respectively. Also, %Al2O3, %BaO, %CaO, %Li2O, and %MgO are the normalized Al2O3 content, Ba content converted into BaO, Ca content converted into CaO, Li content converted into Li2O, and Mg content converted into MgO, respectively. If the normalized aggregate carbon content is %C and the aggregate carbon content in 100% by mass of the mold powder is %C', the following formula is also established. %C=%C´÷A×100……(3-9)

[0028] The same applies when the mold powder further contains unavoidable impurities. For example, when the unavoidable impurities are composed of SiO2 and the SiO2 content in 100 mass% of the mold powder is %SiO2', the following formula is used instead of the above formula (3-1). A=%TC´+%Al2O3´+%BaO´+%CaO´+%Li2O´+%MgO´+%F´+%SiO2´……(3-10) Furthermore, the content of unavoidable impurities, %Im, coincides with the normalized SiO2 content (%SiO2) and is calculated by the following formula: %Im=%SiO2=%SiO2´÷A×100……(3-11)

[0029] Next, the reasons for limiting each component will be explained.

[0030] [Aggregate carbon] The aggregate carbon plays a role in adjusting the melting speed of the powder. Examples of the aggregate carbon include, but are not limited to, carbon black and coke powder. The content of the aggregate carbon will be described later.

[0031] If the total C content is low, the effect as aggregate cannot be obtained. From such a viewpoint, the total C content is preferably 1.3% or more. On the other hand, if the total C content exceeds 5.0%, when the thermite reaction occurs, C burns and a flame occurs, which may cause equipment failure and operation stoppage. Therefore, from the viewpoint of preventing operation trouble, the total C content is preferably 5.0% or less. Here, the total C content can be obtained as the sum of the aggregate carbon content and the C content derived from carbonates described later. In addition, the C derived from carbonates is considered to be the sum of the C derived from carbonates remaining in the premelt raw material described later and the C derived from carbonates blended other than the premelt raw material. The total C content can be measured by a combustion method.

[0032] [Al2O3] Al2O3 is added to increase the activity of Al2O3 in the molten powder and suppress the oxidation reaction of Al in the molten steel. If the Al2O3 content is less than 25%, such an effect cannot be obtained. Therefore, the Al2O3 content is set to 25% or more, preferably 28% or more. The Al2O3 content may be 25.0% or more, or may be 28.0% or more. On the other hand, if the Al2O3 content is higher than 35%, the solidification start temperature of the powder becomes very high, taking into consideration that the Al2O3 content will further increase during casting. Therefore, the Al2O3 content is set to 35% or less, preferably 33% or less. The Al2O3 content may be 35.0% or less, or may be 33.0% or less. The Al2O3 content is determined by converting the Al content determined by fluorescent X-ray analysis into Al2O3.

[0033] [At least one oxide selected from the group consisting of CaO, BaO, MgO, La2O3, and ZrO2] As a result of the study by the present inventors, it was found that the powder solidification start temperature can be lowered by including at least one oxide selected from the group consisting of CaO, BaO, MgO, La2O3, and ZrO2. This is believed to be due to the following reasons. First, all of the oxides have a standard free energy of formation lower than Al2O3 at 1300°C. The average temperature of the powder in the molten state poured into the mold is 1300°C. Here, since oxides having a standard free energy of formation lower than Al2O3 at 1300°C hardly react with Al in the molten steel, the increase in the Al2O3 concentration of the powder during casting is suppressed. Furthermore, the oxides form a composite oxide with Al2O3, lowering the solidification start temperature of the powder. Therefore, in order to suppress the increase in the Al2O3 concentration and lower the solidification start temperature of the powder, it is necessary to include an oxide having a standard free energy of formation lower than Al2O3 at 1300°C. For the above reasons, in one embodiment of the present invention, the powder contains at least one oxide selected from the group consisting of CaO, BaO, MgO, La2O3, and ZrO2.

[0034] [Total content of Ca, Ba, Mg, La, and Zr calculated as oxide: 40 to 60 mass%] If the total content of Ca, Ba, Mg, La, and Zr in terms of oxide is less than 40%, the above-mentioned effect of suppressing the increase in Al2O3 concentration and lowering the solidification start temperature of the powder cannot be obtained. Therefore, the total content is set to 40% or more, preferably 45% or more. The total content may be 40.0% or more, or 45.0% or more. On the other hand, if the total content exceeds 60%, the content of other components will be reduced instead, and the effect of containing other components will not be obtained. Therefore, the total content is set to 60% or less, preferably 55% or less. The total content may be 60.0% or less, or 55.0% or less. The total content is calculated by determining the content of Ca, Mg, La, and Zr elements by fluorescent X-ray analysis, and the content of Ba element by ICP emission spectroscopy, converting them into CaO, MgO, La2O3, ZrO2, and BaO, and then adding them up.

[0035] Among the oxides, CaO, BaO and MgO are excellent in terms of cost, and can form a liquid phase at a low temperature more efficiently even when the Al2O3 in the powder is increased. From this viewpoint, it is preferable that the oxide is at least one component selected from the group consisting of CaO, BaO and MgO. In this case, the total content of Ca, Ba and Mg calculated as oxide is preferably 40% or more, more preferably 45% or more. The total content may be 40.0% or more, or may be 45.0% or more. On the other hand, the total content is preferably 60% or less, more preferably 55% or less. The total content may be 60.0% or less, or may be 55.0% or less.

[0036] The upper and lower limits of the respective contents of Ca and Ba are not particularly limited. However, the Ca content in terms of CaO may be 20.0% or more. The Ca content in terms of CaO may be 45.0% or less. The Ba content in terms of BaO may be 10.0% or more. The Ba content in terms of BaO may be 35.0% or less.

[0037] In addition, the upper and lower limits of the respective contents of Mg, La, and Zr are not particularly limited. However, these elements have the effect of lowering the melting point. Therefore, when Mg is contained, the content of Mg in terms of MgO is preferably 1.0% or more. When La is contained, the content of La in terms of La2O3 is preferably 0.5% or more. When Zr is contained, the content of Zr in terms of ZrO2 is preferably 0.5% or more. On the other hand, if it is contained excessively, the melting point increases. Therefore, the content of Mg in terms of MgO is preferably 5.0% or less. The content of La in terms of La2O3 is preferably 3.0% or less. The content of Zr in terms of ZrO2 is preferably 3.0% or less.

[0038] [Fluorine compounds] The fluorine compound is blended to lower the powder solidification start temperature and viscosity described later. The fluorine compound is not particularly limited, and examples thereof include fluorides such as CaF2, LiF, and BaF2. At least one selected from the group consisting of CaF2, LiF, and BaF2 can be used, but it is preferable to use CaF2 from the viewpoint of cost.

[0039] [F content: 3~10% by mass] If the F content of the powder is less than 3%, the above-mentioned effects of the fluorine compound cannot be obtained. Therefore, the F content of the powder is set to 3% or more. The F content may be 3.0% or more. On the other hand, if the F content of the powder exceeds 10%, not only will the effect saturate, but the risk of oxidation and deterioration of the continuous casting machine will increase dramatically. Therefore, the F content of the powder is set to 10% or less. The F content may be 10.0% or less. The F content can be measured using absorptiometry.

[0040] [LiO] Li2O has a higher standard free energy of formation at 1300℃ than Al2O3, but is an oxide that is relatively difficult to reduce by Al, and is also added because it has the effect of lowering the solidification start temperature.

[0041] [Li content in terms of Li2O: 6 to 12 mass%] If the Li content in terms of Li2O is less than 6%, the effect of lowering the solidification start temperature is not exhibited. Therefore, the Li content in terms of Li2O is set to 6% or more, preferably 8% or more. The content may be 6.0% or more, or 8.0% or more. On the other hand, if the Li content in terms of Li2O exceeds 12%, Li2O is easily reduced by Al in the molten steel, and Al2O3 increases, so that the effect of increasing the solidification start temperature due to the increase in Al2O3 exceeds the effect of lowering the solidification start temperature due to the blending of Li2O. Therefore, the Li content in terms of Li2O is set to 12% or less, preferably 11% or less. The content may be 12.0% or less, or 11.0% or less. The content is calculated by determining the content of Li element by ICP emission spectroscopy and converting it to Li2O.

[0042] [Carbonate of at least one element selected from the group consisting of Li, Ca, Ba, Mg, La, and Zr] The powder may contain a carbonate of at least one element selected from the group consisting of Li, Ca, Ba, Mg, La, and Zr. This is for the following reason. In the production of powder, the component composition of an intermediate raw material such as a premelt raw material may deviate from the target. In such a case, the content of the element can be adjusted by mixing the carbonate with the intermediate raw material. Here, even if elements such as Li, Ca, Ba, Mg, La, and Zr are contained as carbonates, the same effect as when the oxide of the element is contained can be obtained.

[0043] When elements such as Ca, Ba, Mg, La, and Zr are contained as carbonates, the total content of the elements calculated as oxides is calculated by adding up the content of the oxides of the elements and the content of the carbonates of the elements calculated as oxides. When Li carbonate is contained, the Li content calculated as Li2O is calculated by adding up the content of Li2O and the content of Li2CO3 calculated as oxides.

[0044] Here, the carbonate may be a carbonate of at least one element selected from the group consisting of Li, Ca, Ba, and Mg, or may be a carbonate of at least one element selected from the group consisting of Li and Ba.

[0045] The total content of the carbonates is not limited as long as the total content of Ca, Ba, Mg, La, and Zr in terms of oxides and the content of Li in terms of Li2O are satisfied. However, by lowering the total content of the carbonates, the content of other components can be increased, and the melting property during casting can be prevented from being changed by carbon dioxide gas. Also, the generation of bare spots can be further suppressed. Therefore, the total content of the carbonates in the powder is preferably 10% or less, more preferably 5% or less. On the other hand, the lower limit of the total content of the carbonates is not particularly limited, and may be 0%, and the carbonates may not be included. From the same viewpoint, the content of Li carbonate in terms of Li2O in the powder is preferably 10% or less. The lower limit of the content is not limited, and may be 0%. From the same viewpoint, for each element of Ca, Ba, Mg, La, and Zr, the content of the carbonate of the element in terms of oxide in the powder is preferably 10% or less. For each element, the lower limit of the content is not particularly limited, and may be 0%.

[0046] From the same viewpoint, the ratio of the content of Li carbonate in terms of Li2O to the content of Li in terms of Li2O is preferably 50% or less. The lower limit of the above ratio is not particularly limited, and may be 0%, and Li carbonate may not be included. From the same viewpoint, the ratio of the content of the carbonate of each element, Ca, Ba, Mg, La, and Zr, in terms of its oxide to the content of the element in terms of its oxide is preferably 50% or less. The lower limit of the above ratio is not particularly limited, and may be 0%, and carbonate of each element may not be included.

[0047] The component composition of the powder according to one embodiment of the present invention has been described above. The powder according to one embodiment of the present invention contains the above components, with the remainder being unavoidable impurities.

[0048] [Total content of the unavoidable impurities: 0 to 2.0% by mass] The unavoidable impurities include oxides (excluding Li2O) whose standard free energy of formation at 1300°C is higher than that of Al2O3. Examples of the oxides include SiO2, Na2O, TiO2, and Fe2O3. Since the oxides may be inevitably mixed into the powder raw materials, it is difficult to completely remove them. However, in order to prevent thermite reaction with Al in the molten steel, it is necessary not to intentionally mix them and to keep the content as low as possible. Therefore, the total content of the unavoidable impurities is set to 2.0% or less.

[0049] [Y:5 or more and 35 or less] In the present invention, it is necessary to determine the component composition of the powder so that Y represented by the above formula (2) is 5 or more and 35 or less.

[0050] First, let us consider the thickness of the molten powder layer during casting. If the thickness of the molten powder layer is less than 5 mm, the flow between the mold and the solidified shell becomes unstable, leading to a localized powder supply shortage and an increased risk of the molten steel coming into direct contact with the mold, a phenomenon known as seizure.

[0051] On the other hand, if the thickness of the molten layer exceeds 35 mm, the following problems arise.

[0052] First, sensor failure makes it difficult to control the molten steel level. Continuous casting machines are usually equipped with a molten steel level detection sensor at the top of the mold to control the molten steel level. If the molten layer becomes too thick, the temperature of the sensor itself will rise, increasing the risk of sensor failure. Continuous casting machines generally control the amount of molten steel poured into the mold while detecting the molten steel level, but if the sensor fails, the automatic control of the molten steel level will stop, and operations will come to a halt.

[0053] In addition, quality problems occur when the powder gets caught in the molten steel. Normally, the molten powder floats on top of the molten steel, with the unmelted powder on top of that, but if the molten layer becomes too thick, the solid phase that precipitates from the molten powder sinks within the molten powder, increasing the risk of it getting caught in the molten steel.

[0054] As a result of investigations by the present inventors, these phenomena were observed only when the molten layer thickness exceeded 35 mm, and therefore the molten layer thickness must be controlled to 35 mm or less.

[0055] Here, the thickness of the molten layer of the powder can be controlled by the melting speed of the powder. That is, if the melting speed is slow, the thickness of the molten layer of the powder becomes thin, and conversely, if the melting speed is fast, the thickness of the molten layer of the powder becomes thick. Also, as mentioned above, the melting speed of the powder can be adjusted by the amount of aggregate added to the powder. As a result of investigating the relationship between the melting layer thickness Y (unit: mm) and the aggregate carbon content %C (unit: mass %) for powders within the composition range of the present invention, it was found that the above formula (2) holds within an error range of 10%.

[0056] In general, the thickness and melting speed of the powder melt layer can be adjusted by changing the components other than the aggregate and the melting point of the powder. However, considering the composition of other components, it is considered that the thickness and melting speed of the powder melt layer in the powder of the present invention are adjusted only by the content of aggregate carbon. That is, in the present invention, by appropriately using a powder having a predetermined composition, the solidification start temperature of the powder between the mold and the solidified shell can be controlled. Here, the solidification start temperature is determined by the composition of the powder after the composition change. On the other hand, the thickness of the powder melt layer in the state of being placed on the molten steel is determined by the composition before the composition change. Therefore, from the viewpoint of controlling both the composition before and after the composition change, it is considered that the thickness and melting speed of the powder melt layer are adjusted only by the content of aggregate carbon.

[0057] Therefore, when the aggregate carbon content expressed in mass % is (%C), Y expressed by the above formula (2) is set to 5 to 35. This makes it possible to produce high quality cast slabs and prevent operational problems. It is preferable that Y is 10 or more. It is also preferable that Y is 30 or less. Here, Y is a value rounded off to the nearest whole number. It is also preferable that the aggregate carbon content is 1.3% or more, and more preferably 1.5% or more. It is preferable that the aggregate carbon content is 3.7% or less, and more preferably 3.5% or less.

[0058] As described above, the powder according to one embodiment of the present invention comprises: Aggregate carbon, Al2O3, At least one oxide selected from the group consisting of CaO, BaO, MgO, La2O3, and ZrO2; Fluorine compounds, LiO, and the balance being unavoidable impurities. Al2O3 content: 25~35% by mass, Total content of Ca, Ba, Mg, La, and Zr calculated as oxide: 40 to 60 mass%, F content: 3~10% by mass, Li content in terms of Li2O: 6 to 12 mass%, The total content of the unavoidable impurities is 0 to 2.0% by mass, When the content of the aggregate carbon expressed in mass % is (%C), it is important that Y represented by the above formula (2) is 5 or more and 35 or less.

[0059] The composition of the components further includes It may contain carbonate of at least one element selected from the group consisting of Li, Ca, Ba, Mg, La, and Zr.

[0060] The powder according to one embodiment of the present invention can be produced, for example, by mixing raw materials to obtain the above-mentioned component composition. Here, the raw materials may be composed of aggregate carbon, Al2O3, at least one oxide selected from the group consisting of CaO, BaO, MgO, La2O3, and ZrO2, a fluorine compound, and Li2O. The raw materials may further contain a carbonate of at least one element selected from the group consisting of Li, Ca, Ba, Mg, La, and Zr. A part or all of the raw materials may be composed of a premelt raw material. The particle size of the powder may be adjusted by a method such as grinding or classification.

[0061] [Premelt raw materials] The premelt raw material refers to a material obtained by melting and pulverizing a raw material in advance. As described above, carbonates such as Li2CO3 and BaCO3 may be blended as raw materials for powder. However, when carbonates are blended, gas is generated by melting the powder during casting, which may adversely affect the quality of the cast piece, such as pinhole defects and inclusion entrapment defects, or may adversely affect the operation, such as melting of the submerged nozzle. The premelt raw material is used to reduce such effects and form a stable molten layer. Therefore, in the powder according to one embodiment of the present invention, it is preferable that 30% by mass or more of the powder is made of premelt raw material, and more preferably 50% by mass or more of the powder is made of premelt raw material. On the other hand, the upper limit of the proportion of the premelt raw material is not particularly limited, and may be 100% by mass. However, considering the blending of aggregate carbon, it is preferable that 99.5% by mass or less of the powder is made of premelt raw material. It is also more preferable that 90% by mass or less of the powder is made of premelt raw material.

[0062] A powder according to an embodiment of the present invention can be prepared by blending additional materials with the premelt raw material in order to adjust the powder's component composition. For example, when Al2O3 is insufficient, Al2O3 can be blended. When CaO is insufficient, CaF2 or CaO can be blended. When F content is insufficient, CaF2 can be blended. When BaO is insufficient, BaCO3 can be blended. When Li2O is insufficient, Li2CO3 can be blended.

[0063] Here, the aggregate carbon cannot be a premelt raw material, i.e., the ratio of the premelt raw material to the total amount of aggregate carbon may be 0%.

[0064] If carbonate is added after premelt for component adjustment, the total C content increases, the content of other components decreases, and the molten state changes due to the influence of carbon dioxide. Furthermore, it may lead to the generation of dust and flames. In other words, by reducing the amount of carbonate added, the operability and quality can be further improved. Therefore, for carbonates of at least one element selected from the group consisting of Li, Ca, Ba, Mg, La, and Zr, the ratio of the carbonate other than the premelt raw material to the total amount of powder is preferably 20% or less, more preferably 10% or less. The lower limit of the ratio is not particularly limited and may be 0%.

[0065] [Particle size] By using finely ground powder, the powder is easily melted during casting, and a stable molten layer is formed. Therefore, the powder according to one embodiment of the present invention preferably has a maximum particle size of 250 μm or less. Here, a maximum particle size of 250 μm or less means that all particles pass through a 60 mesh (250 μm opening) standard sieve (SIK THE IIDA TESTING SIEVE) specified in JIS Z 8801. In other words, the powder preferably has a particle size that all particles pass through a 60 mesh sieve.

[0066] [Steel manufacturing method] A method for producing steel according to one embodiment of the present invention will be described below. The method for producing steel according to one embodiment of the present invention is a method for continuously casting steel containing 0.5 mass % or more of Al using the above powder.

[0067] In the continuous casting of high Al steel, the use of the above powder can minimize the occurrence of thermite reactions, and high Al steel of stable quality can be produced with high productivity. Therefore, the steel subjected to continuous casting by the steel production method according to one embodiment of the present invention contains 0.5 mass % or more of Al, preferably 1.0 mass % or more. In other words, the steel production method according to one embodiment of the present invention is a method for continuously casting steel containing 0.5 mass % or more of Al, preferably a method for continuously casting steel containing 1.0 mass % or more of Al.

[0068] [Solidification start temperature] In order to produce high-quality cast pieces while preventing operational problems in continuous casting, it is advantageous to lower the solidification start temperature of the powder during casting. Lowering the solidification start temperature results in higher quality cast pieces and further reduces the risk of operational problems.

[0069] The average temperature of the molten powder during casting is 1300° C. Therefore, it is preferable that the powder start to solidify at or below 1300° C. In other words, it is preferable to control the powder so that it becomes completely liquid at 1300° C. during casting.

[0070] [viscosity] Furthermore, according to the present invention, in order to produce high-quality cast slabs, it is preferable to lower the viscosity of the powder at 1300°C during casting (hereinafter, the viscosity of the powder at 1300°C during casting may be simply referred to as viscosity). This is because lowering the viscosity at 1300°C, which is the average temperature in the molten state, ensures uniform flow when the powder is added, and reduces unevenness on the cast slab surface. From this perspective, it is preferable to control the viscosity to 10 Poise or less. Note that 1 Poise = 0.1 Pa s.

[0071] The solidification start temperature and viscosity are measured as follows: First, the molten powder is sampled during casting. Since the measured values ​​fluctuate in the early stages of casting due to the ongoing compositional change of the powder, the sample is sampled immediately before the end of the casting period when the compositional change of the powder has reached a steady state.

[0072] Next, the solidification start temperature and viscosity are measured. The solidification start temperature can be measured using differential thermal analysis. Specifically, the sample is cooled from the molten state at a constant cooling rate, the differential heat peak is measured using differential thermal analysis, and the starting point on the high temperature side of the peak (peak starting temperature) is taken as the solidification start temperature. The viscosity can also be measured using a rotational viscometer.

[0073] [Melted layer thickness] As described above, in the continuous casting of high Al steel, it is preferable that the thickness of the molten layer is 5 mm or more and 35 mm or less. The thickness of the molten layer can be measured, for example, by inserting a copper wire into the powder, removing it, and then observing the state of the deposits.

[0074] [Powder consumption] In a method for producing steel according to an embodiment of the present invention, the powder is added to the meniscus when molten steel, which has been melted to have the above-mentioned Al content, is poured from a ladle into a mold through a tundish. After being supplied to the meniscus, the powder is molten, penetrates into the gap between the mold and the solidified shell, and is pulled out to the rear of the mold together with the slab. In this continuous casting process, the molten steel and the powder come into contact with each other at the meniscus, and the Al in the molten steel reacts with the powder only while the contact is occurring. Therefore, if the powder consumption is small, the reaction time with the molten steel per unit amount of powder becomes long, and the Al2O3 concentration of the powder increases, so that the solidification start temperature becomes high. Furthermore, if the powder consumption is small, the viscosity at 1300°C becomes high due to the increase in Al2O3, which brings about high viscosity.

[0075] Here, the reaction between the powder and molten steel does not reach equilibrium instantly, but changes gradually, and the components in the powder saturate at a certain value lower than the equilibrium value. Here, the balance equation for component i in the powder is expressed as follows using the powder consumption amount. W (dX i / dt)=Q P ·(X i,0 -X i )+k i ·A·(X i,E -X i )……(4-1) W: Powder melt layer weight (kg) X i : Concentration of component i in the powder X i,0 : initial concentration of component i in the powder X i,E : Equilibrium concentration of component i between molten steel and powder t: time (s) Q P : Powder consumption (kg / s) A: Reaction area between molten steel and powder (m 2 ) k i : reaction rate constant of component i (kg / m 2 / s) Here, the concentration of component i no longer changes (dX i / dt=0), the concentration of component i is X i can be expressed as follows: X i =(Q P X i,0 +k i ·A·X i,E ) / (Q P +k i A)……(4-2) From the above formula, the powder consumption Q P By increasing, X i In other words, if component i is Al2O3, by increasing the powder consumption, the increase in Al2O3 during casting is diluted, the Al2O3 concentration at saturation decreases, and a low solidification start temperature and low viscosity are achieved.

[0076] Therefore, in order to further reduce the solidification initiation temperature and viscosity and realize a more stable operation, it is advisable to increase the powder consumption.

[0077] The inventors have found that, in continuous casting of steel containing 0.5% by mass or more of Al, if powder is charged at a powder consumption rate of less than 0.4 kg per ton of molten steel, the solidification start temperature exceeds 1300°C. On the other hand, by charging the powder according to one embodiment of the present invention at a powder consumption rate of 0.4 kg or more per ton of molten steel, the solidification start temperature can be made 1300°C or lower and the viscosity can be made 10 Poise or lower. This allows stable operation and the production of cast slabs with no problems in surface quality.

[0078] From this viewpoint, in a steel production method according to an embodiment of the present invention, it is preferable to set the powder consumption amount per ton of molten steel to 0.4 kg or more.

[0079] The method for controlling the powder consumption is not particularly limited. However, since the mold generally vibrates in the casting direction, it is preferable to control the powder consumption by the amplitude or frequency of the vibration of the mold. The powder consumption may also be controlled by adjusting the physical properties of the powder. Specifically, the powder consumption can be controlled by adjusting the viscosity and crystallization temperature. The vibration conditions of the mold, such as the amplitude or frequency, may also be changed according to the physical properties of the powder. EXAMPLES

[0080] Next, the present invention will be described in more detail based on examples. However, the present invention is not limited to the following examples, and appropriate modifications can be made within the scope of the present invention, and all of these modifications are included in the technical scope of the present invention.

[0081] First, 12 kinds of mold powders for continuous casting having the composition shown in Table 1 were prepared. In the preparation, alumina (Al2O3), quicklime (CaO), fluorite (CaF2), barium carbonate (BaCO3), magnesium carbonate (MgCO3), and lithium carbonate (Li2CO3) were mixed as necessary, and then melted to prepare a premelt raw material. Next, alumina, quicklime, and fluorite were mixed with the premelt raw material as necessary, and aggregate carbon was further mixed to obtain the composition shown in Table 1. Carbon black was used as the aggregate carbon. Powder C was further mixed with SiO2 and Na2O. The contents of Al, Ca, Mg, and Si were measured by X-ray fluorescence analysis. The total C content was measured by a combustion method. The contents of Ba, Li, and Ti were measured by ICP emission spectrometry. The Na content was measured by atomic absorption spectrometry. The F content was measured by absorptiometry. The values ​​for Al2O3, Li2O, CaO, BaO, MgO, SiO2, Na2O, and TiO2 in Table 1 indicate the content of each element converted to oxide. In addition, carbonates are converted to oxides by the premelt, and the raw materials added after the premelt are all oxides or fluorides, so there is almost no carbon derived from carbonates in any of the powders. Therefore, the total C in Table 1 corresponds to the amount of carbon added as aggregate. The proportion of premelt raw materials in all of the powders shown in Table 1 is 50% or more, and the maximum particle size is 250 μm or less in all cases.

[0082] [Table 1]

[0083] Next, molten steel with a C concentration of 0.0040% and an Al concentration of 5% was produced, and continuous casting of a slab with a mold cross-sectional size of 200 mm x 1000 mm was performed under the condition of a slab withdrawal speed of 0.7 m / min. At this time, the powder shown in Table 2 was supplied while adjusting the vibration conditions of the mold so that the powder consumption per ton of molten steel was as shown in Table 2. In addition, two stages of thermocouples (upper and lower thermocouples) were inserted in the mold at positions 90 mm and 200 mm below the molten steel surface. When casting is performed without problems, the temperature of the upper thermocouple is higher than that of the lower thermocouple, but when the molten steel directly contacts the mold, the temperature of the upper thermocouple and the lower thermocouple are reversed. If the temperatures are reversed, there is a risk of breakout, so the slab withdrawal speed was reduced during casting, and the casting speed was returned to normal after the temperature of the thermocouples stabilized.

[0084] Next, the solidification start temperature and viscosity were measured by the above-mentioned method. In addition, to evaluate the operational aspect, the occurrence of smoke and flames during continuous casting was investigated. In addition, the number of bleeds (pieces / m) was measured by observing the obtained cast pieces. 2 ) was investigated. Furthermore, the trimming yield was investigated as an evaluation of the quality of the slab. The trimming yield is a value calculated by the following formula (5). Trimming yield (%) = (weight of slab after trimming) / (weight of slab before trimming) × 100 … (5) When defects such as depressions occur on the slab surface, a trimming operation is performed to remove the defects by scraping the slab surface with a scarf or grinder, which reduces the yield. In other words, the higher the trimming yield, the higher the quality of the slab.

[0085] The results are shown in Table 2. In the comparative example No. 4, breakout occurred about 10 minutes after the start of casting. Therefore, it was not possible to collect molten powder during casting, and it was not possible to measure the solidification start temperature and viscosity. In addition, it was not possible to evaluate the number of bleeds and the maintenance yield. In the comparative example No. 8, corrosion progressed throughout the continuous casting equipment, making it difficult to continue using it. In the comparative example No. 9, due to an insufficient thickness of the molten powder layer, molten steel was burned onto the mold immediately after the start of casting, and a breakout occurred from the burned area. Therefore, it was not possible to collect molten powder during casting, and it was not possible to measure the solidification start temperature and viscosity. In addition, it was not possible to evaluate the number of bleeds and the maintenance yield. In the comparative example No. 10, the sensor for detecting the molten steel level broke down about 5 minutes after the start of casting, and casting was stopped. Therefore, it was not possible to collect molten powder during casting, and it was not possible to measure the solidification start temperature and viscosity. In addition, it was not possible to evaluate the number of bleeds and the maintenance yield. In the comparative example No. 13, no particular operational troubles were observed during casting, and the number of bleeds in the cast pieces and the trimming yield were the same as in the inventive example, but the steel material after rolling had many powder defects, which are a type of surface defect. This was because the thick molten layer caused many powder entrapments.

[0086] [Table 2]

[0087] As shown in Table 2, all of the inventive examples were able to achieve high quality cast slabs and stable operation, whereas all of the comparative examples either had inferior quality or experienced more operational problems.

[0088] The relationship between the thickness of the molten layer in the above continuous casting and the number of times the temperature of the upper and lower thermocouples reversed is shown in Figure 1. When the molten layer was 5 mm or thicker, the above phenomenon never occurred, but when it was 4 mm thick, it occurred frequently, and casting was stopped when the number of times reached 8.

[0089] In addition, powder defects were investigated after rolling the slabs obtained by the above-mentioned continuous casting. Figure 2 shows the relationship between the molten layer thickness in the above-mentioned continuous casting and the number density of powder defects. When the molten layer thickness was 35 mm or less, almost no powder defects were found in the steel after rolling, but when the molten layer thickness was 36 mm, the number of powder defects due to powder entrapment increased sharply. When the molten layer thickness was 40 mm, casting was stopped midway through casting because the sensor for detecting the molten metal level broke down, but when the slabs that had been cast partway were rolled to produce steel, many powder defects were found.

Claims

1. Aggregate carbon, <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> 、 CaO, BaO, MgO, La 2 O 3 , and ZrO 2 At least one oxide selected from the group consisting of: Fluorine compounds, Li 2 O、 and the remainder being unavoidable impurities, A 2 O 3 Content: 25-35% by mass, Total content of Ca, Ba, Mg, La, and Zr calculated as oxide: 40 to 60 mass%; F content: 3 to 10% by mass, Li's Li 2 Content in terms of O: 6 to 12 mass% The total content of the inevitable impurities is 0 to 2.0% by mass, A mold powder for continuous casting, wherein Y, represented by the following formula, is 5 or more and 35 or less, when the content of the aggregate carbon expressed in mass% is (%C). Y=-12.7×(%C)+51.8

2. The composition further comprises 2. The mold powder for continuous casting according to claim 1, which contains a carbonate of at least one element selected from the group consisting of Li, Ca, Ba, Mg, La, and Zr.

3. 2. The mold powder for continuous casting according to claim 1, wherein the maximum particle size of the mold powder is 250 μm or less.

4. 3. The mold powder for continuous casting according to claim 2, wherein the maximum particle size of the mold powder is 250 μm or less.

5. The mold powder for continuous casting according to any one of claims 1 to 4, wherein 30 mass% or more of the mold powder is made of a premelt raw material.

6. A method for producing steel, comprising continuously casting steel containing 0.5 mass% or more of Al using the mold powder for continuous casting according to any one of claims 1 to 4.

7. A method for producing steel, comprising continuously casting steel containing 0.5 mass % or more of Al using the mold powder for continuous casting according to claim 5.

8. The method for producing steel according to claim 6, wherein the powder consumption per ton of molten steel is 0.4 kg or more.

9. The method for producing steel according to claim 7, wherein the powder consumption per ton of molten steel is 0.4 kg or more.

Citation Information

Patent Citations

  • Continuous casting mold flux for automobile sheet

    CN104707959A

  • High titanium oxide casting powder for continuous casting of titanium-containing steel

    CN111531140A

  • Mold powder for continuous casting

    JP1993185195A

  • Powder for continuous casting for producing b-containing steel and method for producing b-containing steel

    JP2002205153A

  • Mold powder for continuous casting

    JP2003033849A